Internet of Things: A Practical Implementation based on a Wireless Sensor Network Approach - Michele Mercaldi; Andrea D’Oria; Davide Murru; Hai-Ning Liang; Ka Lok Man; Eng Gee Lim; Hahanov, V. I.; Mischenko, A. (EWDTS, 2012)
In this paper we present an introduction and an overview of the Internet of Things concept and its possible realization of an infrastructure based on a Wireless Sensor Network. Our proposed solution aims for memory and power consumption efficiency. Similarly, our proposed implementation is informed by (1) open technology standards; (2) accessibility and reachability; and (3) multi functionality and modularity. In addition, we place emphasis on the use of very low power devices and communication protocols. Internet of Things (IoT), a term first coined by Kevin Ashton in 1999 , is used to refer to uniquely identifiable objects (or more broadly things) and their virtual representations, similar to the network of websites in an internet. The idea is to have all things tagged and, if that were the case, they could be identified and inventoried by computers. If this could be implemented, it will transform drastically our way of life —waste will be reduced significantly; stores will not run out of stock; and stolen items could be easily located. A main component of IoT infrastructure is “smart objects” which are objects that hold a unique identifier. The identifier will allow the objects to be located, enable them to interact with their surrounding environment, and let them communicate with each other for data exchange and collaboration. Within the IoT paradigm, smartness is not only for objects but includes the nature of the networks that connect them. To build smart objects, we need sensors, actuators, radio-frequency identification (RFID) tags, etc. Applications of IoT include domotics, industrial application, nature and environmental monitoring. Even after more than a decade since it was first coined, the implementation of a system of IoT has yet to become a reality. In this paper we proposed a plausible implementation of an IoT system or infrastructure based on a wireless sensor network (WSN) approach. We propose hardware and software possibilities to support such an infrastructure.
Keywords: Internet of Things; A Practical Implementation based; Wireless Sensor Network Approach; IoT